A dictionary of epidemiology - Porta, Miquel; Greenland, Sander; Hernan, Miguel; Silva, Isabel dos Santos; Last, John M. ‫ (Oxford University Press, 2014)
This edition is the most updated since its inception, is the essential text for students and professionals working in and around epidemiology or using its methods. It covers subject areas - genetics, clinical epidemiology, public health practice/policy, preventive medicine, health promotion, social sciences and methods for clinical research